The Hopelessness Level of 3rd Grade Elementary Mathematics Preservice Teachers' and Their Perspectives about Future - ŞENGÜL, SARE (ELSEVIER SCIENCE BV, 2014)
The aim of this study is to determine the hopelessness level of 3rd grade elementary mathematics preservice teachers and their perspectives about future at agovernment university in 2011 - 2012 academic year. The sample of the study is 73 elementary preservise teacher. Because the existing situation aimed to be determine screening model used. The 20 item Beck Hopelessness scale scale that was generated by Beck et. al (1974), and raliability and validity test was made by Seber (1991) and Durak (1994) is used to determine the hopelessness level of 3rd grade elementary mathematics preservice teachers and their perspectives about future. The hopelessness interval is determined by calculating the avarage score. 4 open ended questions are also asked. Suggestions made in accordance with the results of teh study. (C) 2013 The Authors. Published by Elsevier Ltd. Selection and/or peer-review under responsibility of Academic World Education and Research Center.
Keywords: Mathematics preservice teachers; hopelessness; future; SUICIDAL IDEATION; PESSIMISM